Arsenic removal from groundwater through iron oxyhydroxide coated waste products. Issue 2 (November 2013) - Abdallah, Elsadig A.M.; Gagnon, Graham A.
Abstract : The goal of this research was to remove arsenic from groundwater supplies via adsorption into media obtained from waste material generated as by-products from glass recycling programs and the seafood industry such as crushed glass and scallop shells. During the course of this research four new adsorbents were developed: ferric hydroxide coated crushed glass (FHCCG); ferric oxide coated crushed glass (FOCCG); ferric hydroxide coated scallop shells (FHCSS); and ferric oxide coated scallop shells (FOCSS). The adsorbents were characterized through evaluation of their structure, surface area, chemical composition, iron content, and coating stability. Efficiency of the adsorbents to remove arsenic from water was examined through batch kinetic and isotherm adsorption experiments. The adsorption capacity of the adsorbents was also evaluated by performing column experiments using real ground waters and a synthetic water. Arsenic removal to a concentration less than 10 μg/L was achieved with the FHCSS and more than 9000 bed volumes of water were treated before the breakthrough point was reached. The research results revealed that scallop shells coated with ferric hydroxideperformed better than crushed glass coated with ferric hydroxide. Both FOCCG and FOCSS had poor arsenic removal compared with FHCSS and granular ferric hydroxide (GFH). Ferric hydroxide coated scallop shells performed similarly to GFH.